New descriptions of North American Taenionema larvae (Plecoptera: Taeniopterygidae) - Stewart, Kenneth W. (Illiesia, 2009)
The larvae of Taenionema have been poorly known, with only partial written descriptions and illustrations available for Taenionema kincaidi (Hoppe) and Taenionema pallidum (Banks), prior to the detailed description of Taenionema pacificum (Banks). Larvae of all 13 North American species were associated beginning in 1983, and comparatively studied to test the proposed generic characters, and to determine if they could be separated with external morphological characters. An expanded generic diagnosis, 112 comparative illustrations, and a provisional key to the 13 species are presented. Separation of larvae to species with the key requires a combination of characters of the 9th sternum of males and females, geographic distribution, and the few other species-specific characters.
Keywords: entomology; Taeniopterygidae; new records; Taenionema; Plecoptera; United States of America; USA; larvae; entomologija; larve; vrbnice; nove vrste